(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
An integration of strategies in conserving declining coral reefs requires a dynamic approach. In this essay, a combination of three technical approaches was applied to a coral reef area of a marine protected area in the northern Straits of Malacca as a science-based ecosystem approach for natural resource conservation measure. Optically-derived physical water quality models of Total Suspended Solids and chlorophyll-a applied to a series of satellite images to assess the distribution of physical water quality and indirect chemical water quality conditions will provide a historical view of the crucial element that governs the coral reef health. It will also provide insights to coral reef ecosystem response to direct pollution from surrounding waters or land-based pollution inputs from adjacent areas. The hydroacoustic signal classification system which measures different hardness and roughness of bottom sediment substrates stores, categorises and manipulates data received, and produces maps of sea-bed types will aid in determining the percentage of live and dead corals, and in the inventory process of applying Limits of Acceptable Change (LAC) for a large scale survey. LAC framework has a broad applicability to complex tourism setting such as marine protected areas where development of measurable objectives defining desired wilderness and the identification of management actions to provide overall quality enjoyment of tourism are possible while preserving the fragile ecosystems of coral reefs. This is considered a science-based ecosystem approach which is viable, cost-effective, time saving and is based mainly on scientific data of a sensitive ecosystem. This integrated approach with its intensity may fulfil the possibility of identifying the actual limits of acceptable change and the designing of implementation actions for our depleting resource.